Control of plane Poiseuille flow using the Kreiss constant - Quénon, Pierre; Whidborne, James F. (Springer, 2023)
This paper examines the effectiveness of a recent method based on Kreiss’s constant minimization for designing output-feedback compensators to control instabilities in a laminar plane Poiseuille flow. The flow dynamics are highly non-normal, subsequently, small disturbances may be substantially amplified and reach large transient values that induce nonlinearities and lead to turbulence, even though such perturbations should eventually decay in a linear flow model. The maximum transient energy growth and the Kreiss constant both convey information regarding this transient behavior. A Kreiss-constant-minimizing controller is obtained and its effectiveness for the plane Poiseuille flow control problem is demonstrated.
Keywords: flow control; Poiseuille flow; Kreiss constant; transient energy growth